Less than : a documentary on poverty in America [videorecording (DVD)] - Gibb, Candy; West, Dana; Beegle, Donna; Carrion, EJ (Dreamscape Media, 2023)
The in-depth look at poverty in America and beyond explores what its causes are, what its effects are, and if there's hope to improve the situation.